Hubungan Aktivitas dan Pemilihan Jenis Makanan oleh Keluarga terhadap Status Gizi Anak Prasekolah di PAUD Kelurahan Baru Jakarta Timur Tahun 2021 - Fitriana Rizki Yanuarni, (2021)
Nutritional problems are a major health problem in the world, including Indonesia. The 2018 Riskesdas data shows that the prevalence of obese children aged 0-5 years in Indonesia is 8% and malnutrition is 10,2%. The factors that cause nutritional problems in general are lack of activity, less variety of food and poor eating frequency. The purpose of the study was to determine the relationship between physical activity, non-physical activity, type of food and eating frequency with nutritional status. Quantitative research method with cross sectional design on 97 preschool children. Data was collected by questionnaire and measurements of weight and height. Data analysis using the chi square test. The result showed that there was a relationship between physical activity (p=0,001), non-physical activity (p=0,001), and eating frequency (p=0,001) with the nutritional status of preschool children, the unrelated variable was type of food (p=0,080). The conclusion of this study is there was a relationship between physical activity, non-physical activity and eating frequency with the nutritional status of preschool children. It is recommended for PAUD as a place of education to teach children to habituate physical activity and good eating patterns.